2017
DOI: 10.1186/s40575-017-0052-6
|View full text |Cite
|
Sign up to set email alerts
|

Lumbosacral stenosis in Labrador retriever military working dogs – an exomic exploratory study

Abstract: BackgroundCanine lumbosacral stenosis is defined as narrowing of the caudal lumbar and/or sacral vertebral canal. A risk factor for neurologic problems in many large sized breeds, lumbosacral stenosis can also cause early retirement in Labrador retriever military working dogs. Though vital for conservative management of the condition, early detection is complicated by the ambiguous nature of clinical signs of lumbosacral stenosis in stoic and high-drive Labrador retriever military working dogs. Though clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 80 publications
(78 reference statements)
0
7
0
Order By: Relevance
“…The study was a retrospective, secondary analysis, exploratory design. Labrador retriever working dogs, aged 11-48 months, that had undergone lumbosacral CT scanning for two, previous research studies were included (29,30). Due to the retrospective nature of the study, institutional animal care, and use committee approval was not required.…”
Section: Dogsmentioning
confidence: 99%
“…The study was a retrospective, secondary analysis, exploratory design. Labrador retriever working dogs, aged 11-48 months, that had undergone lumbosacral CT scanning for two, previous research studies were included (29,30). Due to the retrospective nature of the study, institutional animal care, and use committee approval was not required.…”
Section: Dogsmentioning
confidence: 99%
“…One study identified a moderate to high heritability of several lumbosacral disease-related anatomical features in the lumbar spine in a large sample of German shepherds (34). Another study identified potential candidate genes for lumbosacral stenosis in a sample of 8 military working Labrador retrievers, and recommended that this candidate gene be further evaluated in larger samples and other breeds (35). Repeating the present study with a larger sample size of dogs would allow a "normal" vs. "affected" population to be established.…”
Section: Discussionmentioning
confidence: 87%
“…Labradors are a very popular household pet dog breed and one of the most common breeds used worldwide as working dogs. Recently studies demonstrated that this breed also has a genetic predisposition to similar diseases to DS such as lumbosacral stenosis (MUKHERJEE et al, 2017) and osteoarthritis (ANDERSON et al, 2018). Other hypothesis that may explain the high prevalence includes the genetic predisposition to obesity (MANKOWSKA et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to humans dog obesity can predispose or exacerbate several clinical conditions such as osteoarthritis, respiratory airway distress, renal diseases, diabetes mellitus and metabolic derangements (IMPELLIZERI et al, 2000;TVARIJONAVICIUTE et al, 2013). Notably both over-nutrition and obesity have been associated with impaired immunity and chronic low-grade inflammation in humans and mouse models (NIEMAN et al, 1999;BERG & SCHERER, 2005). In fact, Anderson et al (2018) reports that breeds at or above mean breed bodyweight were 2.3 times more likely to have osteoarthritis than dogs below average weight.…”
Section: Discussionmentioning
confidence: 99%